2012
DOI: 10.1165/rcmb.2012-0014oc
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between Classical and Alternative NF-κB Pathways Regulates Proinflammatory Responses in Epithelial Cells

Abstract: The transcription factor NF-kB has been causally linked to inflammatory lung diseases. Recent studies have unraveled the complexity of NF-kB activation by identifying two parallel activation pathways: the classical NF-kB pathway, which is controlled by IkB kinase complex-b (IKKb) and RelA/p50, and the alternative pathway, which is controlled by IKKa and RelB/p52. The alternative pathway regulates adaptive immune responses and lymphoid development, yet its role in the regulation of innate immune responses remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 50 publications
2
27
1
Order By: Relevance
“…Here, we show that over-expression of the non-canonical pathway effector p52 does not cause inflammation on its own, but in the setting of LPS treatment can enhance inflammatory cell influx into the lungs, although it is likely that the inflammatory cell infiltrate is an indirect effect of epithelial cell death and altered barrier function. While other studies have suggested that p52 cooperates in regulating inflammatory cytokines in airway epithelial cells (7), we observed no differences in inflammatory cytokine production. In contrast, RelB over-expression led to increased inflammatory cell recruitment, which was not enhanced further by p52 over-expression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here, we show that over-expression of the non-canonical pathway effector p52 does not cause inflammation on its own, but in the setting of LPS treatment can enhance inflammatory cell influx into the lungs, although it is likely that the inflammatory cell infiltrate is an indirect effect of epithelial cell death and altered barrier function. While other studies have suggested that p52 cooperates in regulating inflammatory cytokines in airway epithelial cells (7), we observed no differences in inflammatory cytokine production. In contrast, RelB over-expression led to increased inflammatory cell recruitment, which was not enhanced further by p52 over-expression.…”
Section: Discussioncontrasting
confidence: 99%
“…We have previously shown that NF-κB signaling in the lung epithelium regulates the inflammatory response after LPS stimulation (6), suggesting that epithelial NF-κB signaling is a critical component of ARDS pathogenesis. Although the role of the non-canonical NF-κB pathway in LPS-induced inflammation is unknown, studies with lung epithelial cells in vitro have shown that LPS stimulation induces non-canonical NF-κB activation with slower and more protracted kinetics compared to canonical NF-κB activation and that non-canonical NF-κB signaling may be important for regulation of pro-inflammatory cytokines (7). …”
Section: Introductionmentioning
confidence: 99%
“…We reveal that NR4A depletion in THP-1 cells results in attenuated MIP-3α with enhanced IL-6 protein secretion, and overexpression of NR4A2 in MEF cells shows the inverse during LPS stimulation. Intriguingly, Tully et al revealed in lung epithelial cells that Relb depletion resulted in enhanced IL-6 production alongside attenuated MIP-3α production (32). Here, we show this phenomenon is paralleled in NR4A-depleted cells, and furthermore, we reveal Relb to be a novel NR4A target gene during LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the classical pathway, stimulation induces IKK activation leading to phosphorylation of IκBα which subsequently is ubiquitinated and degradated. After posttranslational modifications, the NF-κB dimer then translocates into the nucleus and binds to κB sites to modulate specific gene expression (14,28,29). There are two IκBα-related mechanisms for inhibiting the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%